Innovation, Regulation and the Digital Environment: The South African Case (Strathmore Law Review, 2017)
It is self-evident that the law, which is often considered to be slow moving at best, has a tendency to lag behind innovation and changes within the system it governs. Despite what appears to be an intrinsic resistance to change, there is much to be said about the legal certainty, the consequential continuity as well as the stability such a system affords those who find themselves within it. In contrast, technology within the digital environment develops and changes at a rapid pace, almost as fast as it proliferates. The innovativeness and productiveness of such an industry often leaves little time for reflection upon salient applicable legal principles involved. Unfortunately, when steps are finally made to modernise the law and to regulate the proliferation of information in such an environment, one seldom finds that the law is implemented smoothly and without conflict or contradiction. This essay attempts to highlight some of these problems and to address a number of the fundamental issues raised by the new policies, amendments and legislation that presume to deal with the digital environment in South Africa.